Prediction of triathlon race time from laboratory testing in national triathletes - Schabort, E. J.; Killian, S. C.; Clair Gibson, A. ST.; Hawley, J. A.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 2000)
Four days after competing in an Olympic-distance National Triathlon Championship (1500-m swim, 40-km cycle, 10-km run), five male and five female triathletes underwent comprehensive physiological testing in an attempt to determine which physiological variables accurately predict triathlon race time. Methods: All triathletes underwent maximal swimming tests over 25 and 400 m, the determination of peak sustained power output (PPO) and peak oxygen uptake (V(dot)O2peak) during an incremental cycle test to exhaustion, and a maximal treadmill running test to assess peak running velocity and V(dot)O2peak. In addition, submaximal steady-state measures of oxygen uptake (V(dot)O2), blood [lactate], and heart rate (HR) were determined during the cycling and running tests. Results: The five most significant (P < 0.01) predictors of triathlon performance were blood lactate measured during steady-state cycling at a workload of 4 W·kg-1 body mass (BM) (r = 0.92), blood lactate while running at 15 km·h-1 (r = 0.89), PPO (r = 0.86), peak treadmill running velocity (r = 0.85), and V(dot)O2peak during cycling (r = 0.85). Stepwise multiple regression analysis revealed a highly significant (r = 0.90, P < 0.001) relationship between predicted race time (from laboratory measures) and actual race time, from the following calculation: race time (s) = -129 (peak treadmill velocity [km·h-1]) + 122 ([lactate] at 4 W·kg-1 BM) + 9456. Conclusion: The results of this study show that race time for top triathletes competing over the Olympic distance can be accurately predicted from the results of maximal and submaximal laboratory measures.